2022
DOI: 10.3389/fendo.2022.1035418
|View full text |Cite
|
Sign up to set email alerts
|

Optimum non-invasive predictive indicators for metabolic dysfunction-associated fatty liver disease and its subgroups in the Chinese population: A retrospective case-control study

Abstract: ObjectiveMetabolic dysfunction-associated fatty liver disease (MAFLD) affects 25% of the population without approved drug therapy. According to the latest consensus, MAFLD is divided into three subgroups based on different diagnostic modalities, including Obesity, Lean, and Type 2 diabetes mellitus (T2DM) MAFLD subgroups. This study aimed to find out the optimum non-invasive metabolism-related indicators to respectively predict MAFLD and its subgroups.Design1058 Chinese participants were enrolled in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…For both sexes, the optimal cut-off values for BMI were lower (27.80 kg/m 2 in males, 28.75 kg/m 2 in female) than the values indicating obesity (> 30 kg/m 2 ). The BMI cutoff points obtained by Jing Liu et al [ 23 ], Cai et al [ 11 ], and Yang et al [ 24 ] were 25.39, 24, and 24.61 kg/m2 respectively, which were lower than our findings. It is well accepted that BMI is closely related to the risk of fatty liver disease and is an important factor in determining negative clinical outcomes [ 10 ].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…For both sexes, the optimal cut-off values for BMI were lower (27.80 kg/m 2 in males, 28.75 kg/m 2 in female) than the values indicating obesity (> 30 kg/m 2 ). The BMI cutoff points obtained by Jing Liu et al [ 23 ], Cai et al [ 11 ], and Yang et al [ 24 ] were 25.39, 24, and 24.61 kg/m2 respectively, which were lower than our findings. It is well accepted that BMI is closely related to the risk of fatty liver disease and is an important factor in determining negative clinical outcomes [ 10 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Our study revealed a strong positive correlation between WC, BMI, BAI, BRI and AVI with HIS, TyG-BMI and TyG-WC, as well as between VAI with AIP, LAP, CMI and TyG Index, as indicated by Pearson’s correlation coefficients. However, some studies have shown that LAP is the best predictor of obese individuals with MAFLD, with the maximum ORs value [ 11 , 23 ]. Also, In a cross-sectional study that included 7968 participants, Yang et al [ 24 ] discovered that TyG-BMI, BMI, TyG, TG/HDL-C, and TG are five significant predictors of the risk of MAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese study revealed WTI had been a positive prognostic value of MetS in both males and females [38] . Furthermore, it should be noted that WTI has been identi ed as a potential indicator for the development of coronary artery disorders [39] and in the occurrence of Metabolic dysfunction-associated fatty liver disease (MAFLD) [40] .…”
Section: Discussionmentioning
confidence: 99%
“…Transient elastography (FibroScan) is a tool used to evaluate liver fatty infltration and fbrosis by measuring liver stifness but not available in routine physical examinations, especially in primary care [6]. Some anthropometric indexes used to diagnose MAFLD are with complex calculations and controversial diagnostic abilities [7]. Terefore, a noninvasive and convenient serum biomarker is required for the classifcation of the MAFLD severity.…”
Section: Introductionmentioning
confidence: 99%